2015
DOI: 10.15562/phpma.v3i2.108
|View full text |Cite
|
Sign up to set email alerts
|

Riwayat Demam Dengue dan Keterlambatan Diagnosis sebagai Faktor Risiko Dengue Shock Syndrome di RSUD Wangaya Denpasar

Abstract: Latar belakang dan tujuan: Demam Berdarah Dengue (DBD) merupakan masalah kesehatan masyarakat di Provinsi Bali terutama di Kota Denpasar dengan angka insiden tahun 2014 sebesar 217,7/100.000 penduduk. Angka tersebut jauh lebih tinggi dari angka insiden nasional sebesar 51/100.000 penduduk. Dengue Shock Syndrome (DSS) masih sering dijumpai dengan kematian yang cukup tinggi. Penelitian ini bertujuan untuk mengetahui faktor risiko DSS pada pasien DBD yang dirawat inap di Rumah Sakit Umum Daerah (RSUD) Wangaya Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In multivariate analysis, the most dominant variable affects the rate of DHF patient recovery was the duration of fever before being treated. Suganda Research (2015) found that the duration of fever before being treated >4 days had a risk occurrence of dengue shock syndrome which can cause death [15].…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, the most dominant variable affects the rate of DHF patient recovery was the duration of fever before being treated. Suganda Research (2015) found that the duration of fever before being treated >4 days had a risk occurrence of dengue shock syndrome which can cause death [15].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of severe DHF in the child age group in Jakarta was reported at 15.32% with a mortality rate of 0.41% 6 . The prevalence of severe DHF in all age groups in Bali was reported at 2.59% 7 . The prevalence of death in the child age group in Yogyakarta was reported to be 27% 8 .…”
Section: Introductionmentioning
confidence: 96%